Menstrual Taboos and Educational Disruption in Nepal: A 10 Year Bibliometric Analysis (2017–2026) - Khadka, Kalpana; Regmi, Pratiksha; Cherry, Jim (NPRC Journal of Multidisciplinary Research, 2026)
Introduction: MHM continues to be one of the key hurdles in achieving equal access to education for adolescent girls in Nepal, especially in communities where harmful cultural practices like Chhaupadi are still prevalent. Although there have been efforts made by policy makers and legal bans implemented, there is no systematic review of literature pertaining to the challenges faced by adolescent girls due to menstrual issues and false beliefs and their effect on secondary education. Methodology: For the purpose of this study, a bibliometric and thematic analysis of peer-reviewed publications indexed in Dimension.ai between January 2017 and April 2026 was performed using a Boolean search string `(“menstruation” OR “chhaupadi”) AND (“education” OR “school” OR “academic”) AND (“girls” OR “adolescent” OR “female students”) AND (“Nepal” OR “Kathmandu” OR “far-western”)`.Data abstraction was based on volume of publications, citation impact, geographical and institutional distribution, co-authorship network analysis (through VOS viewer software), and thematic analysis through generating word clouds. Results: Volume of publications started at 3 articles per year for 2017 before hitting a peak of 20 in 2024, with a total of 428 citations being recorded up to 2025. Nepal ranked highest in terms of documents (58), but it is the United States (920 citations) and the United Kingdom (636 citations) that ranked top in citation impact. Tribhuvan University was the top-most productive institution (21 documents), but it ranked very low in terms of citation density (43 citations overall), while Johns Hopkins University made 438 citations from two documents. Co-authorship analysis showed a tight-knit network of 28 authors involving both Nepalese researchers and colleagues from the United States, the United Kingdom, and Sweden. Word cloud analysis indicated that dominant themes were knowledge (100), study (95), mentorship (90), health (85), education (80), and hygiene (75). School absenteeism is still influenced by misconceptions and the practice of the Chhaupadi ritual, even after its legalization in 2017. Conclusion: Studies focusing on menstruation, Chhaupadi, and secondary education among girls in Nepal have developed into a widely cited field that includes international collaboration. Yet, there is a remarkable disparity between high local production rates and low local citation rates, pointing to a lack of visibility on the part of Nepalese research. It will be critical in future research to pursue urban-rural comparative analysis, mentoring programs, and WASH facilities in schools. The government needs to ensure that existing laws against Chhaupadi are being implemented.